Evaluasi Tingkat Kebisingan di Perpustakaan Kampus: Studi Kuantitatif Berdasarkan Pengukuran dan Analisis Akustik - A'yun, Qurrotul (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
A quiet learning environment is essential for supporting concentration and academic productivity. One of the main challenges in library spaces is the presence of noise, which can disrupt user comfort. This study aims to measure and evaluate noise levels in the Library of UIN Sunan Ampel Surabaya (UINSA) Gununganyar as part of an effort to improve the acoustic quality of study areas. A descriptive quantitative approach was employed, using a Benetech GM1356 sound level meter set to A-weighting (dBA), and data were analyzed using the Equivalent Continuous Sound Level (Leq) method. Measurements were conducted at seven observation points across two floors of the library over three working days (Monday, Wednesday, and Friday) and three time intervals (morning, midday, and afternoon), resulting in a total of 252 data points. The results indicate that the first floor recorded an average noise level of 54.57 dB, which remains within the acceptable limit for learning environments (≤55 dB). In contrast, the second floor exhibited a significantly higher average noise level of 61.98 dB, exceeding the recommended threshold by +6.98 dB. The elevated noise levels on the second floor are attributed to its open-plan layout, the absence of acoustic partitions, and furniture arrangements that promote active interaction. To foster a more conducive learning environment, the study recommends spatial reorganization, the installation of acoustic barriers, and the integration of sound-absorbing materials.